Attributional Style and Burnout of Counselors‐in‐Training. (18th December 2018) - Lee, Injung; Bardhoshi, Gerta; Yoon, Eunhui; Sandersfeld, Tyler; Rush, Roma D.; Priest, Jacob B.
Abstract : The authors examined whether attributional style could explain burnout among 201 counseling graduate students. Hierarchical multiple regression analysis results indicated that stability and globality of attribution explain a significant amount of the variance in counselor trainees' burnout. These findings suggest intervention and training should be used to promote a more flexible and positive orientation to handle stressful life events.